Inoculação de soja com bactérias diazotróficas após períodos de manejo das culturas de inverno - Ferreira, Matheus Martins (2022)
Cover crop residues and co-inoculation (inoculation with Bradyrhizobium and Azospirillum) can influence nodulation, growth and grain yield in soybean. This influence can be positive or negative, depending on the cover plant and the biomass management period before crop sowing. The objective was to evaluate winter cover crops, cover crop biomass management periods and inoculation types on nodulation, growth and yield of soybean. Field experiments were conducted in the 2019/20 and 2020/21 crops season, and in a greenhouse in 2020. In the field, treatments involved two winter cover plants: wheat (TG) and forage turnip (NB); three management periods of cover plants before soybean sowing: 30, 45 and 60 days and two types of inoculation: (only Bradyrhizobium) and coinoculação (Bradyrhizobium e Azospirillum). In the greenhouse, the treatments involved four cover crops: TG, NB, vetch (EV) and control (TS); three management periods of biomass: 30, 45 and 60 days and two types of inoculation: inoculation and coinoculation. The number and dry mass of nodules, root and shoot dry mass, number of pods, soybean grain yield and soil density were evaluated. Coinoculation provided better results for the number of nodules when TG was grown in winter. In the field, NB outperformed TG for soil density and soybean yield. The best management period of the cover crop biomass was 30 days before soybean sowing. For the use of diazotrophic bacteria in soybean, especially when co-inoculation with Azospirillum brasilense is performed, the type of cover crop and the biomass management period should be considered. Co-inoculation of soybean is improved by using winter wheat and managing the biomass close to sowing the crop.